The target of rapamycin kinase affects biomass accumulation and cell cycle progression by altering carbon/nitrogen balance in synchronized Chlamydomonas reinhardtii cells - Jüppner, Jessica; Mubeen, Umarah; Leisse, Andrea; Caldana, Camila; Wiszniewski, Andrew; Steinhauser, Dirk; Giavalisco, Patrick (The Plant journal : for cell and molecular biology, 2018)
Summary Several metabolic processes tightly regulate growth and biomass accumulation. A highly conserved protein complex containing the target of rapamycin (TOR) kinase is known to integrate intra‐ and extracellular stimuli controlling nutrient allocation and hence cellular growth. Although several functions of TOR have been described in various heterotrophic eukaryotes, our understanding lags far behind in photosynthetic organisms. In the present investigation, we used the model alga Chlamydomonas reinhardtii to conduct a time‐resolved analysis of molecular and physiological features throughout the diurnal cycle after TOR inhibition. Detailed examination of the cell cycle phases revealed that growth is not only repressed by 50%, but also that significant, non‐linear delays in the progression can be observed. By using metabolomics analysis, we elucidated that the growth repression was mainly driven by differential carbon partitioning between anabolic and catabolic processes. Accordingly, the time‐resolved analysis illustrated that metabolic processes including amino acid‐, starch‐ and triacylglycerol synthesis, as well RNA degradation, were redirected within minutes of TOR inhibition. Here especially the high accumulation of nitrogen‐containing compounds indicated that an active TOR kinase controls the carbon to nitrogen balance of the cell, which is responsible for biomass accumulation, growth and cell cycle progression. Significance Statement Growth and development are controlled by a few regulatory proteins, which sense environmental conditions and translate this information into intracellular molecular responses. Target of Rapamycin is one of the central regulatory proteins controlling several metabolic, especially biosynthetic, processes. In the current study, we elucidate the influence of Target of Rapamycin activity on biomass accumulation, cellular growth, cell cycle and central carbon and nitrogen metabolism in the photoautotrophically growing alga Chlamydomonas reinhardtii.